Prevalence and histopathological characterization of Masai Giraffe (Giraffa camelopardalis tippelskirchi) skin disease in Tarangire-Manyara ecosystem, Northern Tanzania. Issue 1 (1st January 2021) - Kiula, Faraja E.; Mjingo, Eblate E.; Mremi, Alex R.; Chilongola, Jaffu O.; Munishi, Linus K.
Abstract: Background: Masai Giraffes have declined dramatically in recent decades due to loss of habitat and illegal hunting. Hence, it is critically important that the epidemiology and etiology of so-called giraffe skin disease (GSD) is understood well. Aim: To assess the prevalence and histopathological characteristics of GSD in the Tarangire-Manyara Ecosystem (TME), northern Tanzania. Methods: The study used road transects to gather field information on GSD. Eighty-four giraffes were sighted by systematic random sampling in the six study sites. Examination of giraffes involved body distribution of lesions, severity of the lesions and whether they were associated with age and sex of the affected giraffes. Five giraffes with GSD were immobilized for tissue collection and histopathological analysis. Results: Prevalence among adults was 79%. Affected animals typically had 1–5 lesions which were mostly moderate and were predominantly observed on the forelegs. GSD positivity rate was higher among females versus males, whereas males had a higher rate of severe lesions and generally had more lesions than females. Calves showed no lesions. All tissue sections from five affected giraffes showed the presence of large quantities of fungal elements (hyphae and spores) that involved hair shafts and sub-cutaneous tissue after staining with Grocott Methenamine Silver as special fungal staining technique. Conclusions: Our findings suggest the involvement of fungal infection in GSD pathogenesis. Clinical relevance: We recommend further characterization of the lesions using modern molecular techniques and culture to identify primary and secondary or opportunistic etiologies, and the order in which the pathogens occur in the lesions.